Spin-label scanning reveals conformational sensitivity of the bound helical interfaces of IA3 - Katie M. Dunleavy; Eugene Milshteyn; Zachary Sorrentino; Natasha L. Pirman; Zhanglong Liu; Matthew B. Chandler; Peter W. D’Amore; Gail E. Fanucci (AIMS Biophysics, 2018)
IA3 is an intrinsically disordered protein (IDP) that becomes helical when bound to yeast proteinase A (YPRA) or in the presence of the secondary stabilizer 2,2,2-trifluoroethanol (TFE). Here, site-directed spin-labeling (SDSL) continuous wave electron paramagnetic resonance (CW-EPR) spectroscopy and circular dichroism (CD) are used to characterize the TFE-induced helical conformation of IA3 for a series of spin-labeled cysteine scanning constructs and varied amino acid substitutions. Results demonstrate that the N-terminal concave helical surface of IA3, which is the buried interface when bound to YPRA, can be destabilized by the spin-label or bulky amino acid substitutions. In contrast, the helical tendency of IA3 is enhanced when spin-labels are incorporated into the convex, i.e., solvent exposed, surface of IA3. No impact of the spin-label within the C-terminal region was observed. This work further demonstrates the utility and sensitivity of SDSL CW-EPR for studies of IDPs. In general, care must be taken to ensure the spin-label does not interfere with native helical tendencies and these studies provide us with knowledge of where to incorporate spin-labels for future SDSL investigations of IA3.